Screening of anti-heart failure active compounds from fangjihuangqi decoction in verapamil-induced zebrafish model by anti-heart failure index approach - Li, Jun; Zhu, Yue; Zhao, Xiaoping; Zhao, Lu; Wang, Yi; Yang, Zhenzhong (Frontiers in Pharmacology, 2022)
Heart failure is the end stage of various cardiovascular diseases. Fangjihuangqi Decoction (FJHQD) is a famous traditional Chinese medicine (TCM) formula, which is clinically effective in the treatment of chronic heart failure. However, the anti-heart failure ingredients of FJHQD have not been clarified, and the related mechanisms of action are rarely studied. In the present study, through quantification analysis of heart rate and ventricular area changes, a heart failure model and cardiac function evaluation system in cardiomyocytes-labelled Tg (cmlc2: eGFP) transgenic zebrafish larvae were constructed, and the anti-heart failure index (AHFI) that can comprehensively evaluate the cardiac function of zebrafish was proposed. Based on this model, FJHQD, its mainly herbs, components and ingredients were evaluated for the anti-heart failure effects. The results showed that FJHQD and its herbs exhibited potent anti-heart failure activity. Furthermore, total alkaloids from Stephaniae Tetrandrae Radix, total flavonoids from Astragali Radix and total flavonoids from Glycyrrhizae Radix et Rhizoma were identified to be the main components exerting the anti-heart failure activity of FJHQD. Then, we screened the main ingredients of these components, and glycyrrhizic acid, licochalcone A and calycosin were found to exhibit excellent cardioprotective effects. Finally, we found that FJHQD, glycyrrhizic acid, licochalcone A and calycosin may improve cardiac function in zebrafish by regulating oxidative stress, inflammatory response and apoptosis-related pathways. Taken together, our findings offer biological evidences toward the anti-heart failure effect of FJHQD, and provide guidance for the clinical application of FJHQD.